METAFORA DALAM PANTUN MELAYU KALIMANTAN BARAT - AR Muzammil (Universitas Tanjungpura, 2022)
Abstract Pantun is an old form of poetry in Malay literature that until now is still used actively in various activities of malay nusantara community life, including in West Kalimantan. Pantun uses many words that mean figurative. This research aims to examine the use of metaphors in West Kalimantan Malay pantun based on two problems, namely from the aspect of type and meaning of metaphors. The research method used is a qualitative descriptive method. The data collection techniques used in this study are interview techniques, recording techniques, and recording techniques. The findings of this study are the types of metaphors contained in the Malay Pantun of West Kalimantan (1) anthropomorphic metaphors, (2) metaphors ofhesion, (3) metaphors from concrete to abstract, and (4) synesthesia metaphors. The metaphorical meaning in the Malay pantun of West Kalimantan generally contains figurative meanings as in comparative compounds. In conclusion from this study, metaphors are used in many West Kalimantan Malay pantun to express the expressivity that characterizes pantun.Keywords: pantun, metaphors, West Kalimantan Malay ABSTRAKPantun merupakan bentuk puisi lama dalam kesusasteraan Melayu yang sampai saat ini masih digunakan secara aktif dalam berbagai aktivitas kehidupan masyarakat Melayu Nusantara, termasuk di Kalimantan Barat. Pantun banyak mengunakan kata yang bermakna kiasan. Penelitian ini bertujuan menelaah penggunaan metafora dalam pantun Melayu Kalimantan Barat berdasarkan dua permasalahan, yaitu dari aspek jenis dan makna metafora. Metode penelitian yang digunakan adalah metode deskriptif kualitatif. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah teknik wawancara, teknik rekam, dan teknik catat. Temuan hasil penelitian ini jenis metafora yang terdapat dalam Pantun Melayu Kalimantan Barat (1) metafora antropomorfik, (2) metafora kehewanan, (3) metafora dari konkret ke abstrak, dan (4) metafora sinestesia. Makna metafora dalam pantun Melayu Kalimantan Barat umumnya mengandung makna kiasan seperti dalam majas perbandingan. Simpulan dari penelitian ini, metafora digunakan dalam banyak pantun Melayu Kalimantan Barat untuk mengungkapkan ekspresivitas yang menjadi ciri khas pantun.Kata kunci: pantun, metafora, Melayu Kalimantan Barat